Carbon Taxes Implementation Policies: Global and European Dimensions - Boneva, Svetla (Research Papers, 2021)
The objective of the research is to analyze the present framework of available carbon taxes worldwide as one of the contemporary methods for cost engineering of carbon dioxide emission. For the achievement of this objective two basic research tasks have been fulfilled: 1) the essence and framework of and the effects stemming from the application of the basic carbon dioxide pricing approaches (the Emissions Trading Systems, Carbon Taxes, Offset Mechanisms, Results Based Climate Finance and Internal Pricing of the carbon emissions) have been presented; and 2) the European Union dimension of the application of a new carbon tax has been discussed within the context of the Carbon border adjustment mechanism (the carbon border tax) of the European union. The research methods that have been used are comparative analysis, content analysis, elements of the retrospective analysis and generalizations of the ideas of main analytical documents in this field. The results of the research are generalizations and analyses providing solid ground for taking evidence-based decisions regarding future carbon taxes introduction at national and EU level as well as for addressing motivated recommendations towards the application of this type of taxes.
Keywords: Carbon taxes; European union carbon border tax